Relocation Of Earthquake Hypocenter In The Flores Region Using Hypo71 - Regolinda Maneno; Bagus Jaya Sentosa; Gazali Rachman (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
Flores is one of the seismically high activity zones of Indonesia region as a consequence of Indo-Australian plate subduction under the Eurasian plate. Tectonic earthquakes required to be studied because in large magnitude it can bring disaster. Therefore the precise of hypocenter determination needs to be done. In this study, hypocenter relocation is done by Single Event Determination method using hypo71. The data used are earthquake event data in Flores area which has magnitude > 4 SR at period between January 2010 and March 2018 obtained from BMKG catalog. Hypo71 requires data of arrival time of P and S waves at the recorder station. The arrival time of P and S waves data at each station is obtained by picking P and S waves using SeisGram2k70. The results showed that the source of the earthquake experienced a change of position both horizontally and vertically. In the vertical direction of hypocenter earthquake changes in the distance between 0.02 - 89.61 km, while in the horizontal direction the hypocenter of the earthquake changes in the distance of 1.11 - 71.11 km. After relocation, the hypocenter of the earthquake distributed along the Back Arc Trust in the northern island of Flores. Hypocenter relocation using hypo71 yields a small residual between the observation time and calculation time denoted by RMS <1.